2009
DOI: 10.1038/sj.bjc.6605329
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Mage-b DNA induces CD8 T-cell responses at young but not old age in mice with metastatic breast cancer

Abstract: BACKGROUND: Elderly individuals react less efficiently to vaccines than do adults, mainly because of T-cell unresponsiveness. In this study, we analysed whether tumour-associated antigen (TAA)-specific CD8 T-cell responses could be induced by vaccination in old mice with metastatic breast cancer. METHODS: The effect of pcDNA-3.1-and Listeria-based vaccines, expressing TAA Mage-b, on Mage-b-specific immune responses was tested in spleens and draining lymph nodes (LNs) of mild (4TO7cg) and aggressive (4T1) synge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 30 publications
(36 reference statements)
1
38
0
Order By: Relevance
“…Vaccination of both models with Mage-b was highly effective against metastases at young but not at old age, and this correlated with strong Mage-b-specific T cell responses in vitro and in vivo at young but not at old age [3]. Interestingly, we found that Mage-b vaccination activated macrophages and NK cells (producing IFNγ) in old mice [3].…”
Section: Improvement Of Cancer Vaccination At Old Age In Preclinical mentioning
confidence: 60%
See 4 more Smart Citations
“…Vaccination of both models with Mage-b was highly effective against metastases at young but not at old age, and this correlated with strong Mage-b-specific T cell responses in vitro and in vivo at young but not at old age [3]. Interestingly, we found that Mage-b vaccination activated macrophages and NK cells (producing IFNγ) in old mice [3].…”
Section: Improvement Of Cancer Vaccination At Old Age In Preclinical mentioning
confidence: 60%
“…Vaccination of both models with Mage-b was highly effective against metastases at young but not at old age, and this correlated with strong Mage-b-specific T cell responses in vitro and in vivo at young but not at old age [3]. Interestingly, we found that Mage-b vaccination activated macrophages and NK cells (producing IFNγ) in old mice [3]. In another more recent vaccine study with Mage-b delivered through a highly attenuated L. monocytogenes, we found a dramatic effect on the metastases in the 4T1 model at young age [40].…”
Section: Improvement Of Cancer Vaccination At Old Age In Preclinical mentioning
confidence: 95%
See 3 more Smart Citations